2023
DOI: 10.3390/educsci13080774
|View full text |Cite
|
Sign up to set email alerts
|

Adapted Education for Gifted Students in Norway: A Mixed Methods Study

Abstract: In this article, we describe the mixed methods research (i.e., quantitative survey and qualitative interviews) we conducted to investigate adapted education for gifted students in Norway. The survey results showed that the teachers (n = 132) used differentiation strategies and agreed that gifted students need an adapted education that extends beyond the regular curriculum. We identified three themes related to adapted education based on an analysis of the student interview data (n = 17, aged 12–15) and four th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…We have found similarities and differences between the school systems in Australia and Norway. Both countries have school systems that value egalitarianism which generates antipathy against elitism and gifted education [1,58]. Egalitarian school systems, out of fear of creating good conditions for elitism, tend not to recognise giftedness among children officially.…”
Section: Teachers' Attitudes To Gifted Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found similarities and differences between the school systems in Australia and Norway. Both countries have school systems that value egalitarianism which generates antipathy against elitism and gifted education [1,58]. Egalitarian school systems, out of fear of creating good conditions for elitism, tend not to recognise giftedness among children officially.…”
Section: Teachers' Attitudes To Gifted Educationmentioning
confidence: 99%
“…The findings from Australian studies by Mullen and Jung [1] are perhaps relevant not only to the Norwegian context but also to the Scandinavian context due to similarities in values concerning egalitarianism. Several studies in Scandinavian countries have shown that schools prioritise inclusive education for students with disabilities over gifted students [3,[58][59][60][61]. In Finland, Tirri and Kuusisto [61] show that there is a greater need to recognize the social and affective needs of gifted pupils.…”
Section: Teachers' Attitudes To Gifted Educationmentioning
confidence: 99%